Reversing Paralysis Technology - Remarkable Breakthrough for the Treatment of Incurable Paralysis - Hasin, F.; Hasan, AKM. B.; Islam, AFM. R.; Hossain, M.M.; Musa, H. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
This research has been developed to study on the Brain Computer Interface (BCI) technology - which is called a Reversing Paralysiss Technology. It is a momentous innovation of medical sector for the treatment of Incurable Paralysis. The purpose of this study was to provide a high level of evidences of the effectiveness and the safety of this technology. The methodology of this study is using a qualitative systematic review method. It was followed by data collection and specific keywords based data searching method. Two renowned research papers indexing database have been employed for locating peer reviewed scientific papers such as Pub-Med Database and Google Scholar Database. Besides this database searching, the Google Search also performed for collecting scientific review news and informations regarding this technology. Researchers analysed all keyword based from the selected literatures, from the clinical trial results and from the new sources; and then summarizes the findings in respect of this technology. In this technology, the scientists have hypothesized that reversing of the paralyzed state of a patient is possible by creating Brain Computer Interfaces (BCIs) in the patient’s body through two brain implants. One implant is placed on the surface of the brain or attached to the brain's cortex. Then, another one is implanted in the spinal cord by passing the injured lesion of spine. These two implants will act as a bridge between the command center (the brain) and the control center (the spine). When the regular communication is established between the brain and the spine, then the paralyzed condition will reverse. The researchers, till to this date have analysed thirty seven (37) peer reviewed literatures, twelve (12) scientific/tech based news review sources and four (4) authentic clinical trial results which had been published in this context. Scientists claimed that this theory is effective and is safe for the treatment of paralysis based on successful clinical trials. Thus, from this extensive qualitative systematic review study, it established a theory that Reversing Paralysis Technology is working through Brain Computer Interfaces - Implants mechanism; and it is an effective and a safe process for patients’ paralysis treatment.